Parent-infant closeness and family-centered care in neonatal intensive care - Raiskila, Simo (fi=Turun yliopisto|en=University of Turku|, 2018)
Abstract Early interaction and closeness with a caregiver are important for the development of newborn infants. Postpartum separation between parent and newborn is still common in the hospital care of premature babies. Parent-infant closeness in neonatal units can be supported by a family-centered care culture, in which hospital care for the newborn is implemented in cooperation with parents. Measuring both parent-infant closeness and family-centered care culture is challenging, and hardly any prospective metrics reported by parents exists in the literature. The aim of this dissertation was to examine a) first the closeness between the infant and parent, b) second the parents’ participation in their infant’s care and how each are supported, and c) third how family-centered care practices are implemented in neonatal intensive care units (NICUs). New measures were developed and tested in order to obtain reliable information on the physical closeness between parent and infant and the perceived quality of family-centered care in NICUs. The results of the present study indicate that it is possible to modify care practices to better support parent-infant closeness and parents’ participation in their infant’s care without endangering the growth of the premature infant or lengthening hospitalization. In a prospective multi-center study including 11 NICUs in 6 European countries, differences among countries as well as among units within the same country were observed. The most significant factor explaining the observed differences was the possibility for parents to stay overnight in the unit. The new methods developed and validated in the present study can be used in the future, for example in studies exploring the effects of parent-infant closeness on short- and long-term outcomes of the hospitalized newborns. With these new tools, it is also possible to support the implementation of FCC practices.

Tiivistelmä Varhainen vuorovaikutus ja läheisyys ovat tärkeä perusta vastasyntyneen kehitykselle. Vanhemman ja vastasyntyneen välistä läheisyyttä sairaaloissa voidaan tukea perhekeskeisellä hoitokulttuurilla (Family-centered care), jossa vastasyntyneen sairaalahoito toteutetaan yhteistyössä vanhempien kanssa. Läheisyyden ja perhekeskeisen hoitokulttuurin mittaaminen on haastavaa ja kirjallisuudesta ei juuri löydy prospektiivisia vanhempien raportoimia mittareita. Tämän väitöstutkimuksen tavoitteena oli selvittää, miten vanhemman ja lapsen välistä läheisyyttä ja vanhempien osallistumista keskosen hoitoon tuetaan ja miten perhekeskeisiä hoitokäytäntöjä toteutetaan vastasyntyneiden teho-osastoilla. Tutkimuksessa kehitettiin ja testattiin uusia mittareita, joilla voidaan saada luotettavaa tietoa vanhemman ja lapsen välisestä fyysisestä läheisyydestä ja perhekeskeisen hoidon laadusta vastasyntyneiden teho-osastoilla. Tutkimuksessa todettiin, että vastasyntyneiden teho-osaston hoitokäytäntöjä voidaan muokata läheisyyttä ja vanhempien osallistumista tukevampaan suuntaan vaarantamatta keskosen kasvua tai pidentämättä sairaalahoitoaikoja. Eurooppalaisessa monikeskustutkimuksessa osoitettiin eroja niin eri maiden välillä kuin myös saman maan sisällä eri yksiköiden välillä. Selkeimmin eroja selittävä tekijä oli vanhempien mahdollisuus yöpyä osastolla. Tutkimuksessa käytetyt prospektiiviset mittarit osoittautuivat helppokäyttöisiksi ja vähän kuormittaviksi, ja pystyivät osoittamaan merkittäviä yksiköiden välisiä eroja. Uusia menetelmiä voidaan tulevaisuudessa hyödyntää esimerkiksi selvitettäessä vanhemman ja lapsen välisen läheisyyden fysiologisia vaikutuksia ja vaikutuksia pitkäaikaiskehitykseen. Kehitettyjen mittareiden avulla voidaan myös tukea perhekeskeisten hoitokäytäntöjen käyttöönottoa.